KINEMATICAL ANALYSIS OF HANG STYLE TECHNIQUE IN LONG JUMP DURING TAKE-OFF (International Journal of Food and Nutritional Sciences, 2022)
Methods: The Purpose of the study was Kinematical Analysis of Hang Style Technique in Long Jump during Take-Off.10 male long jumpers (in which, 5 right & 5 left take-off foot of the subjects) National/Inter university level athletes from Sub Centre Sports Authority of India, Lucknow; Guru Gobind Singh Sports College, Lucknow, Diesel Locomotive Workshop; Varanasi and Banaras Hindu University Varanasi who’s age ranging between 16 to 28 years. The purpose of the study was explained to the subjects and requested to jump in their best effort during each take-off attempt. The data was analyzed by using two Casio EX-F1 high speed camera was used, which have frequency from 60 to300 frames per second (f/s).The data were recorded from sagittal plane and frontal plane. Camera-1 was placed perpendicular from the subjects at a distance of 8.80 meters and above from ground 1.40 meter height. Camera-2 placed perpendicular to camera-1 and in front of subject performing the Take-off in hang style technique at the distance 11.30 meters and above from ground 1.40 meter.Results: The present study carried out on the National/Inter university level athletes from Sub Centre Sports Authority of India, Lucknow; Guru Gobind Singh Sports College, Lucknow, Diesel Locomotive Workshop; Varanasi and Banaras Hindu University Varanasi. After analyzing the data and results, it may be concluded that the right Angular Kinematical Variables shows the average performance of the long jumpers. Another left kinematic variables also shows average performance of the long jumpers the National/Inter university level athletes from Sub Centre Sports Authority of India, Lucknow; Guru Gobind Singh Sports College, Lucknow, Diesel Locomotive Workshop; Varanasi and Banaras Hindu University Varanasi